Familial Pancreatic Cancer and the Future of Directed Screening - Welinsky, Sara (Gut Liver, 2017)
Pancreatic cancer (PC) is the third most common cause of cancer-related death in the United States and the 12th most common worldwide. Mortality is high, largely due to late stage of presentation and suboptimal treatment regimens. Approximately 10% of PC cases have a familial basis. The major genetic defect has yet to be identified but may be inherited by an autosomal dominant pattern with reduced penetrance. Several known hereditary syndromes or genes are associated with an increased risk of developing PC and account for approximately 2% of PCs. These syndromes include the hereditary breast-ovarian cancer syndrome, Peutz-Jeghers syndrome, familial atypical multiple mole melanoma, Lynch syndrome, familial polyposis, ataxia-telangiectasia, and hereditary pancreatitis. Appropriate screening using methods such as biomarkers or imaging, with endoscopic ultrasound and magnetic resonance imaging, may assist in the early detection of neoplastic lesions in the high-risk population. If these lesions are detected and treated before the development of invasive carcinoma, PC disease morbidity and mortality may be improved. This review will focus on familial PC and other hereditary syndromes implicated in the increased risk of PC; it will also highlight current screening methods and the future of new screening modalities.